Maternal Choline Supplementation During Gestational Diabetes Causes Long-Term Phenotypic Changes in Offspring (P11-132-19) - Korsmo, Hunter (Curr Dev Nutr, 2019)
OBJECTIVES: Using a mouse gestational diabetes mellitus (GDM) model, this study investigated whether maternal choline supplementation (MCS) could alter postnatal growth and metabolic abnormalities associated with GDM. METHODS: C57BL/6 mice were either fed a low fat (LF, 10kcal % fat) control diet or a high fat (HF, 60kcal % fat) diet prior to and during pregnancy to induce GDM. These mice received either 25mM choline (MCS) or plain drinking water, After weaning, offspring were fed the HF diet for 6 weeks before glucose tolerance testing and dissection. RESULTS: In male offspring from MCS-GDM mothers, we observed a decrease in fasting blood glucose levels and an increase in glucose tolerance when comparing to other groups (P < 0.05). Liver choline metabolite measurements demonstrated that free choline content was lower (P = 0.01) in the MCS-GDM male offspring than control GDM male offspring; there is also an increase in liver sphingomyelin concentrations (P = 0.007) in female offspring from MCS-GDM compared to control GDM dams. CONCLUSIONS: MCS during GDM leads to improvements in blood glucose control in male mouse offspring exposed to a postnatal HF environment. FUNDING SOURCES: NIGMS and NIDDK; New York Academy of Sciences.